High levels of serum uric acid are associated with microvascular complications in patients with long-term diabetes - Hanying Wang; Liping Gu; Yuhang Ma; Xindan Xing; Yuan Qu; Xin Shi; Xinyi Liu; Hancong Wan; Qian Zhu; Yingchen Shen; Chong Chen; Li Su; et al. (Diabetology & Metabolic Syndrome)
Abstract Aims To assess the association between serum uric acid (SUA) level and the prevalence of diabetic retinopathy (DR) and chronic kidney disease (CKD) in patients with long-term diabetes. Methods A cross-sectional analysis was conducted involving diabetic patients from Shanghai General hospital during October 2018 and October 2021. Participants underwent measurements of SUA, renal function test and DR assessments via fundus photography. Multivariable ordinal logistic regression models assessed odd ratios (ORs) and 95% confidence intervals (95% CIs) for the progression of DR and CKD. Receiver operating characteristics (ROC) curves identified SUA thresholds, categorizing participants into low and high SUA groups. Results Among the 1015 patients with diabetes, SUA levels were higher in individuals with advanced CKD stages (p < 0.001, compared with stage 1 CKD) and vision-threatening diabetic retinopathy (VTDR) (p = 0.019, compared with no diabetic retinopathy (NDR)). In multivariable models adjusted for potential confounders, higher SUA levels were associated with an increased risk of DR (OR: 1.002, 95% CI: 1.001–1.004) and CKD (OR: 1.008, 95% CI: 1.006–1.011). Notably, SUA levels exceeding 354.0 µmol/L (95% CI: 318.9–393.2) and 361.0 µmol/L (339.2–386.3) were associated with 1.571-fold (95% CI: 1.139–2.099, P = 0.006 for DR) and 1.395-fold (95% CI: 1.033–1.885, P = 0.030 for CKD) increased risks, respectively. Gender-specific analyses also demonstrated a positive correlation between higher SUA levels and the incidence of DR and CKD in both males and females. Conclusions Elevated SUA levels are independently coincided with increased risks of DR and CKD, suggesting that SUA may serve as a potential risk marker for diabetic complications.